Analysis of Minimum Service Standards and Passenger Satisfaction for the Electric Train (KRL) on the Cikarang–Sudirman Commuter Line - Maruddhany, Rhystya Atysya; Sudjatmiko, Eddy Triyanto; Prihartono, Prihartono (President University, 2024)
KRL is a public transportation system is in the great interest of the Indonesian because it is considered effective and efficient for the community and can be a solution to streamline the mobility of the population, especially for the populace in the Jabodetabek region. As the number of passengers increases every year, it is important to know the services and facilities provided by the operator. This research aims to determine the quality of services and facilities of this transportation mode, both at the station and during the trip. The study examines the KRL Commuter Line service between Cikarang and Sudirman, with Sudirman Station selected as a representative sample for analysis. The analysis is made in accordance with Regulation of the Minister of Transportation No. 63 of 2019, and the level of customer satisfaction is analyzed using the Important Performance Analysis/IPA method and Customer Satisfaction Index/CSI. The research indicates that the services at Sudirman Station comply with most of the minimum standards outlined in the regulation, however some facilities need to be provided such as full platform roof, customer work desk and elevator or lift for disable. While on the train, CCTV and first aid kit need to be installed. According to the IPA method, there are attributes of service that need to be enhanced on the primary priority scale: (1) the height/width difference of the station platform floor and the railroad floor; (2) seating facilities in the waiting room; (3) passenger service facilities such as work desks; (4) a special elevator (lift) for passengers using wheelchairs; (5) availability of a first aid kit in each train set; (6) space capacity to carry standing maximum of 1 m2Â for 6 people; (7) availability of CCTV in the train; and (8) punctuality of departure or arrival time. In addition, the CSI score for KRL Sudirman station's quality of service performance is 71.60%, indicating that customers are satisfied with the quality of service provided.